2002
DOI: 10.1006/hbeh.2002.1799
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli from Conspecifics Influence Brain Mast Cell Population in Male Rats

Abstract: It is well established that mast cells occur within the brain of many species, and that the brain mast cell population is not static, but changes with the behavioral and physiological state of the animal.In this study, we tested whether exposure to conspecifics alters the number of brain mast cells in male rats, and then investigated the nature of stimuli influencing the changes observed in the number and localization of brain mast cells. Five days of cohabitation with an ovariectomized, estrogen-progesterone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 61 publications
(70 reference statements)
1
18
0
4
Order By: Relevance
“…The decreased body weight by E 2 coincided with that observed in previous studies [41][42][43]. E 2 administration did not affect the food intake per body weight.…”
Section: Discussionsupporting
confidence: 90%
“…The decreased body weight by E 2 coincided with that observed in previous studies [41][42][43]. E 2 administration did not affect the food intake per body weight.…”
Section: Discussionsupporting
confidence: 90%
“…Psychological stressors induced through social defeat and isolation stress increased the number of mast cells in the brain (26,63). Last, gonadal hormones from conspecifics during mating also increase mast cell number and activation in the brain (23,62,64).…”
Section: Mast Cells Are Active Both Constitutively and Following Stimmentioning
confidence: 99%
“…However, the function of mast cells in the brain is unknown. A role in normal physiology and behavior is suggested as the brain population of mast cells fluctuates with endocrine status and changes after stress and handling (23)(24)(25)(26). Not surprisingly, there are individual differences in the number of brain mast cells within species (27), perhaps associated with behavioral and/or experiential differences.…”
mentioning
confidence: 99%
“…3 and 4). Because a previous study had shown that increases in brain mast cells following cohabitation in rats are specific to a particular rostrocaudal extent of the thalamus (Asarian et al, 2002), the distribution of thalamic mast cells was investigated. Mast cells were distributed uniformly throughout the rostrocaudal extent of the thalamus across groups, with most cells being observed in the paraventricular thalamic region directly below the medial habenula.…”
Section: Methodsmentioning
confidence: 99%
“…In male mice, mast cells increase in discrete thalamic nuclei following mating and cohabitation with a female conspecific (Yang et al, 1999). As in male mice, mast cells increase in sensory, motor, and limbic thalamic regions in male rats following prolonged pairing with an estrogen-progesterone-primed female (Price, 1995;Asarian et al, 2002). Additionally, male Syrian hamsters housed in long day lengths or exposed to conspecific vaginal secretions display elevated brain mast cell numbers (Novak et al, 1994;Novak and Nunez, 1995).…”
Section: Introductionmentioning
confidence: 99%